Biplane fluoroscopy for hindfoot motion analysis during gait: A model-based evaluation. (May 2017) - Cross, Janelle A.; McHenry, Benjamin D.; Molthen, Robert; Exten, Emily; Schmidt, Taly Gilat; Harris, Gerald F.
Highlights: The accuracy of a biplane fluoroscopy system was validated for model-based tracking. Static trials had overall RMS error of 0.43 ± 0.22 mm and 0.66 ± 0.43°. Dynamic trials had overall RMS error of 0.59 ± 0.10 mm and 0.71 ± 0.12°. Intra-observer error had overall RMS error of 0.62 ± 0.12 mm and 0.66 ± 0.14°. Abstract: The purpose of this study was to quantify the accuracy and precision of a biplane fluoroscopy system for model-based tracking of in vivo hindfoot motion during over-ground gait. Gait was simulated by manually manipulating a cadaver foot specimen through a biplane fluoroscopy system attached to a walkway. Three 1.6-mm diameter steel beads were implanted into the specimen to provide marker-based tracking measurements for comparison to model-based tracking. A CT scan was acquired to define a gold standard of implanted bead positions and to create 3D models for model-based tracking. Static and dynamic trials manipulating the specimen through the capture volume were performed. Marker-based tracking error was calculated relative to the gold standard implanted bead positions. The bias, precision, and root-mean-squared (RMS) error of model-based tracking was calculated relative to the marker-based measurements. The overall RMS error of the model-based tracking method averaged 0.43 ± 0.22 mm and 0.66 ± 0.43° for static and 0.59 ± 0.10 mm and 0.71 ± 0.12° for dynamic trials. The model-based tracking approach represents a non-invasive technique for accurately measuring dynamic hindfoot joint motion during in vivo, weight bearing conditions. The model-based tracking method is recommended for application on the basis of the study results.